The results of many years of complex use of cycle- and power-ergometry in determining the physical capacity of young athletes - M. F. Khoroshukha; A. I. Bosenko; Ye. L. Mykhaliuk; M. M. Filippov (Сучасні медичні технології)
Aim of the work: to assess the results of a complex use of cycle- and power-ergometry in determining the aerobic and anaerobic-aerobic performance in young athletes for the selection of criteria in predicting athletes’ sports abilities and performance results at competitions in certain sports.